Transformative role of artificial intelligence in promoting nurses’ mental resilience and quality of care delivery: from burden to balance - Sharma, Swati; Pritika; Kumar, Pradhyumn; Badduri, Phanindrareddy; Anusha, Sivakumar; Lucas, Prerna; Vandali, Vijayaraddi; Appireddygari, Surekha; Prabha, N.; Tongpangkokla Ozukum, S.; S., Saravanan; Umar, Mohammed (International Journal of Research in Medical Sciences, 2025)
The transformative integration of artificial intelligence (AI) in nursing practice has emerged as a crucial innovation to mitigate occupational stress, enhance psychological resilience, and improve the overall quality of care delivery. As healthcare systems face mounting workloads, AI-driven technologies-such as machine learning, affective computing, and predictive analytics-offer meaningful pathways to achieve a balance between technological precision and human compassion. This systematic review critically synthesizes global evidence on AI’s role in promoting nurses’ mental resilience and optimizing patient-centered care outcomes. Following PRISMA 2020 and Joanna Briggs institute (JBI) guidelines, five major electronic databases-PubMed, Scopus, CINAHL, Web of Science, and Cochrane Library-were systematically searched for studies published between 2014 and 2024. A total of 78 studies met the inclusion criteria after rigorous screening, quality appraisal, and ROBINS-I/CASP bias assessment. Thematic and quantitative analyses revealed that AI interventions resulted in an average 28-35% improvement in resilience and a 22-32% enhancement in care quality. Among intervention types, simulation-based AI and affective computing yielded the highest combined benefits, while automation and predictive analytics consistently enhanced operational efficiency. Additionally, governance frameworks contributed indirectly to fostering ethical confidence and long-term trust in AI adoption. Overall, the findings underscore AI’s transformative potential in harmonizing innovation with empathy, empowering nurses toward sustainable well-being and professional excellence. When implemented responsibly, AI redefines modern nursing-from burden to balance-anchored in emotional intelligence, ethical stewardship, and evidence-based precision.